Jejunal bacterial overgrowth and intestinal permeability in children with immunodeficiency syndromes. Issue 8 (August 1990) - Pignata, C; Budillon, G; Monaco, G; Nani, E; Cuomo, R; Parrilli, G; Ciccimarra, F
Abstract : Seventeen paediatric patients with immunodeficiency syndromes (10 with selective IgA deficiency, four with panhypogammaglobulinaemia, and three with selective T cell deficiency) were investigated for bacterial overgrowth of the small intestine and gut permeability to macromolecules. Five of 12 patients showed viable bacterial counts of more than 2 x 10(5)/ml in jejunal fluid. Bacterial overgrowth was also confirmed indirectly by breath hydrogen determination, which was higher than 10 ppm in four of the five patients with positive jejunal culture. Gut permeability to lactulose and L-rhamnose was abnormal in 16 of the 17 immunodeficient patients, who also had higher mean urinary excretion ratios than control subjects-mean (SD) values were 0.216 (0.160) and 0.029 (0.002), respectively. These studies indicate that bacterial overgrowth of the small intestine is a common feature in immunodeficient patients, regardless of the immunological abnormality. Moreover, these patients have an increased gut permeability to macromolecules.